PerFlexMEA: a thin microporous microelectrode array for in vitro cardiac electrophysiological studies on hetero-cellular bilayers with controlled gap junction communication. Issue 9 (7th May 2015) - Mondal, A.; Baker, B.; Harvey, I. R.; Moreno, A. P.
<x xml:space="preserve">Abstract</x> Micropores in the ultra-thin parylene membrane limit myocyte–nonmyocyte interactions without transmembrane cell migration. Microelectrodes record field potentials for computing electrical conduction of the myocyte layer.